Design and Development of a Web Based Accounting Information System at TB Alam Lestari - Rahardjo, Ervina Febriani; Sanjaya, Ridwan; Koeswoyo, G. Freddy (Journal of Business and Technology, 2024)
TB Alam Lestari is a store that selling some building material. In this store, there are some problems, such as missing invoice, don’t have financial statement, and different quantities during stock opname. Objective of this research is to design and implement accounting information system at TB Alam Lestari. To achieve the objective, researcher made accounting information system with RAD method. The result of this research is the owner of TB Alam Lestari starts to record transaction digitally, save the invoice automatically, have product quantity reference when stock opname, and have financial statement.